European Code against Cancer 4th Edition: Environment, occupation and cancer. (December 2015) - Espina, Carolina; Straif, Kurt; Friis, Søren; Kogevinas, Manolis; Saracci, Rodolfo; Vainio, Harri; Schüz, Joachim
Abstract: People are exposed throughout life to a wide range of environmental and occupational pollutants from different sources at home, in the workplace or in the general environment – exposures that normally cannot be directly controlled by the individual. Several chemicals, metals, dusts, fibres, and occupations have been established to be causally associated with an increased risk of specific cancers, such as cancers of the lung, skin and urinary bladder, and mesothelioma. Significant amounts of air pollutants – mainly from road transport and industry – continue to be emitted in the European Union (EU); an increased occurrence of lung cancer has been attributed to air pollution even in areas below the EU limits for daily air pollution. Additionally, a wide range of pesticides as well as industrial and household chemicals may lead to widespread human exposure, mainly through food and water. For most environmental pollutants, the most effective measures are regulations and community actions aimed at reducing and eliminating the exposures. Thus, it is imperative to raise awareness about environmental and occupational carcinogens in order to motivate individuals to be proactive in advocating protection and supporting initiatives aimed at reducing pollution. Regulations are not homogeneous across EU countries, and protective measures in the workplace are not used consistently by all workers all the time; compliance with regulations needs to be continuously monitored and enforced. Therefore, the recommendation on Environment and Occupation of the 4th edition of the European Code against Cancer, focusing on what individuals can do to reduce their cancer risk, reads: " In the workplace, protect yourself against cancer-causing substances by following health and safety instructions ."